Quality of life and its relationship to future anxiety among secondary school students in Sebha, Libya."A field study" (Journal of Human Sciences, 2021)
The current study aimed to reveal the relationship between quality of life and future anxiety among secondary school students in sebha city. The study tools from the quality of life scale prepared by: saleh fouad al-shaarawy 2002 and the future anxiety scale prepared by: zainab shukair 2005, also-* the current study followed the descriptive, correlative approach for its suitability to the objectives and nature of the research. The data was processed statistically through the statistical program (spss), and the results resulted in: there is a negative statistically significant relationship between quality of life and future anxiety, meaning whenever the student does not have a quality of life, this leads to his suffering from future anxiety. Several future studies and recommendations have also been proposed.